Ukraine in International Systems for Measuring Gender Inequality - Krasnikova, K. V.; Skoryk, M. M. (Statistics of Ukraine, 2021)
The article contains a complete list of global and regional instruments for measuring gender inequality relevant to Ukraine with global indices at the forefront, as well as international gender equality assessment systems and data portals available at the global, regional and sectoral levels. The structure of each of the five global complex and eight global sectoral gender indices from among those covering Ukraine was analyzed: Gender-related Development Index, GDI; Gender Gap Index, GGI; Social Institutions and Gender Index, SIGI; Gender Inequality Index, GII; The SDG Gender Index, SDGGI; Women, Business and the Law Index, WBLI; Women’s Economic Opportunity Index, WEO; Gender Budgeting Indicator, GBI; Women, Peace, and Security Index, WPSI; Gender Social Norms Index, GSNI; Women’s Power Index, WPI; The Female Opportunity Index 2021, FOI2021; Gender Parity Index, GPI. The sub-indicators of these indices were analyzed, in fourteen thematic areas identified in accordance with the Convention on the Elimination of All Forms of Discrimination against Women (CEDAW). Areas were ranked according to the level of their coverage by global data presented in the indices. Thematic gender data portals were analyzed and a list of nine sectoral global data was compiled, in particular for Ukraine: Gender data by DHS Program; Gender Data Portal (GenderStats) by The World Bank; Institute for Democracy and Electoral Assistance (IDEA) Gender Quotas Database; The World Inequality Database on Education (WIDE); Gender, Institutions and Development Database; Inter-Parliamentary Union’s: Women in Parliament; ILOStat Labour Statistics on Women; Digital Gender Gaps; Barro-Lee Educational Attainment Dataset. Based on the results of the analysis, key thematic areas of women’s rights were identified and ranked, whether or not covered by global gender data, on which the indices were built. These areas are: Employment; Political and social life (covered by nine indices out of thirteen relevant to Ukraine); Education (by eight indices, respectively); Commitment to eliminate discrimination (by seven indices); Economic and social life (by six indices); Health care and family planning (by five indices). Areas where the gender situation may remain unclear due to the lack of global data and the lack of international comparisons have been identified, namely: Temporary special measures; Participation at the international level; Marriage and family life. These areas are covered by only two indices out of thirteen. The thematic area “Women and girls from rural areas” is the least covered by global data and is indexed in only one index out of thirteen. It is concluded that these last thematic areas will be particularly dependent on national statistics and will be in dire need of data.